Mechanistic insights into rare-earth-catalysed C–H alkylation of sulfides: sulfide facilitating alkene insertion and beyond. Issue 22 (5th May 2022) - Zhou, Yu; Wu, Ping; Cao, Fanshu; Shi, Lei; Zhang, Ni; Xue, Zuqian; Luo, Gen
Abstract : The alkene insertion via the heteroatom-containing substrate facilitated mechanism were computationally revealed in rare-earth-catalyzed C–H alkylation of sulfides and other heteroatom-containing substrates such as pyridines and anisoles. Abstract : The catalytic C–H alkylation with alkenes is of much interest and importance, as it offers a 100% atom efficient route for C–C bond construction. In the past decade, great progress in rare-earth catalysed C–H alkylation of various heteroatom-containing substrates with alkenes has been made. However, whether or how a heteroatom-containing substrate would influence the coordination or insertion of an alkene at the catalyst metal center remained elusive. In this work, the mechanism of Sc-catalysed C–H alkylation of sulfides with alkenes and dienes has been carefully examined by DFT calculations, which revealed that the alkene insertion could proceed via a sulfide-facilitated mechanism. It has been found that a similar mechanism may also work for the C–H alkylation of other heteroatom-containing substrates such as pyridine and anisole. Moreover, the substrate-facilitated alkene insertion mechanism and a substrate-free one could be switched by fine-tuning the sterics of catalysts and substrates. This work provides new insights into the role of heteroatom-containing substrates in alkene-insertion-involved reactions, and may help guide designing new catalysis systems.